Pengembangan Perangkat Pembelajaran IPA Berbasis Discovery Learning untuk Menuntaskan Hasil Belajar Siswa - Rohmawati, Imaya; Basir, Rian Sang (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This research aims was to produce a decent learning device IPA (valid, practical, and effective) to complete the learning outcomes in human circulatory system material. To achieve these objectives, the authors developed a learning device that consists of a syllabus, lesson plans, worksheet, Instructional Materials for Students and Student Assessment Instrument using 4-D model of development. This learning device validated and revised before it tested on twenty five students of seven grader of SMP Negeri 1 Blitar with one group pretest-posttest design. In analyzing data, this study used observation, test, and questionnaire. The technique of analyzing data used descriptive qualitative and quantitative design. The result of the study showed that first, the learning device was valid. Second, teaching and learning activity done well. Third, learning outcome was 100% complete. Fourth, students gave positive response with excellent category. Based on the findings, it could be concluded that the learning device for science subject with discovery learning based had been valid, practical, and effective it could be used to complete the learning outcomes of students.